2018
DOI: 10.1371/journal.pone.0209338
|View full text |Cite
|
Sign up to set email alerts
|

The downregulation of lncRNA EMX2OS might independently predict shorter recurrence-free survival of classical papillary thyroid cancer

Abstract: Homeobox protein Emx2 is a transcription factor that is encoded by the EMX2 gene. In this study, using data from the Cancer Genome Atlas-Thyroid Cancer (TCGA-THCA), we aimed to examine the expression profile of EMX2 and its antisense transcript EMX2OS in papillary thyroid cancer (PTC), their prognostic value and potential regulatory networks. Results showed that in the three variants of PTC, EMX2 was significantly downregulated in classical PTC, while EMX2OS were significantly downregulated in follicular and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…In recent years, many studies based on the bioinformatics analysis were conducted to predict the RFS. Gu et al reported that decreased EMX2OS (homeobox protein) expression might be a valuable prognostic biomarker of unfavorable RFS in classical PTMC [56], while Gong et al found that preserved SCN4B might be a prognostic marker of favorable RFS in classical PTMC [57]. In general, the similar recurrence rate and RFS between the two groups in our systematic review and meta-analysis might be caused by the limited number of the study, small sample and insufficient follow-up time.…”
Section: Discussionmentioning
confidence: 64%
“…In recent years, many studies based on the bioinformatics analysis were conducted to predict the RFS. Gu et al reported that decreased EMX2OS (homeobox protein) expression might be a valuable prognostic biomarker of unfavorable RFS in classical PTMC [56], while Gong et al found that preserved SCN4B might be a prognostic marker of favorable RFS in classical PTMC [57]. In general, the similar recurrence rate and RFS between the two groups in our systematic review and meta-analysis might be caused by the limited number of the study, small sample and insufficient follow-up time.…”
Section: Discussionmentioning
confidence: 64%
“…including AC005104.1, AC093278.2, AC098484.1, AL360181.2, LINC01011, AP001372.2, AC007637.1, AL354733.3, and AP001189.3, which were the first time that served as markers in the current research. The lncRNA EMX2OS, which has been validated and identified to potentially induce proliferation and invasion, and promote sphere formation in ovarian cancer cells by regulating the miR-654-3p/AKT3/PD-L1 Axis 28 Additionally, EMX2OS can be used as a biomarker in laryngeal cancer and papillary thyroid cancer 29,30 . Furthermore, SPINT1-AS1 was identified as a potential marker www.nature.com/scientificreports/ in the prognosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown, however, to be highly expressed in hepatocellular carcinoma and inhibited the transcription of THBS1 by recruiting DNMT3b to its promoter region [34]. Previous research has revealed that the downregulation of EMX2OS in classical papillary thyroid cancer might independently predict shorter recurrence-free survival [35], while the overexpression of EMX2OS in ovarian cancer and EMX2OS/miR-654/AKT3 axis may target PD-L1(programmed cell death protein 1) to suppress the initiation and progression of cancer [36].…”
Section: Discussionmentioning
confidence: 99%